2008
DOI: 10.1109/tmag.2008.921951
|View full text |Cite
|
Sign up to set email alerts
|

Partial Demagnetization of Permanent Magnets in Electrical Machines Caused by an Inclined Field

Abstract: We report a study of partial demagnetization of axially pressed sintered Nd-Fe-B magnets by inclined pulse demagnetization measurements, including a recoil behavior of the Nd-Fe-B material. From these measurements, we develop a simple empirical model for demagnetization of Nd-Fe-B magnets caused by an inclined field. We calculate demagnetization of a simple surface-magnet machine and a two-pole high-speed machine by using an exponent function-based model, taking also the inclined demagnetizing field into accou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 7 publications
1
37
0
Order By: Relevance
“…Checking demagnetization in the current time step should be more time consuming since it will affect the calculation of the current step in each iteration. When checking for demagnetization, only the magnetic flux density parallel to the magnetization direction (here denoted y) was considered, since this has proven to work well for multi-pole machines, and it is hard to quantify the angular dependence [19,29]. Another difference between the models is that the Jacobian (the system matrix) had to be manually defined in the external function.…”
Section: Simulation Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Checking demagnetization in the current time step should be more time consuming since it will affect the calculation of the current step in each iteration. When checking for demagnetization, only the magnetic flux density parallel to the magnetization direction (here denoted y) was considered, since this has proven to work well for multi-pole machines, and it is hard to quantify the angular dependence [19,29]. Another difference between the models is that the Jacobian (the system matrix) had to be manually defined in the external function.…”
Section: Simulation Modelsmentioning
confidence: 99%
“…Faults in electrical machines is a common research topic, and there are several studies on demagnetization during different kinds of overload conditions [7,18,19]. However, it is very hard to recognize all possible faults, not only from a technical but also from an economical point of view.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 3D FE static analysis is carried out for two values of peak armature currents 20 A and 200 A, corresponding to the full load and ten times the full load respectively. In [10], the authors proved that both antiparallel and perpendicular field components to the direction of magnetization are necessary to accurately estimate the level of demagnetization. Therefore, |H| and not |B| field distribution is [24], [25], the authors concluded that the edges and area of permanent magnet exposed to air gap are more susceptible to demagnetization than the inner volume.…”
Section: Estimation Of Demagnetization Level Of Ferrite Magnet Inmentioning
confidence: 99%
“…Although the recoil curve will experience a slight bend upwards the linear model used and presented here is considered to be good enough [9], [10].…”
Section: Development Of Fem Modelmentioning
confidence: 99%